2,4-Dinitrophenyl phenyl sulfone - Ellena, J. (1996)
The crystal structure of the title compound, C12H8-N2O6S, has been determined by single-crystal X-ray diffraction. The compound crystallizes in the noncentrosymmetric P21 space group. The substituted aromatic ring has a slightly deformed boat conformation. The ο-NO2 and p-NO2 groups are twisted out of the plane of the phenyl ring. The unsubstituted aromatic ring is planar and the dihedral angle between the mean plane of the rings is 71.1 (2)○. Short C - H⋯O intermolecular contacts stabilize the three-dimensional structure.